2017
DOI: 10.7181/acfs.2017.18.4.292
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyomatous Mesenchymal Hamartoma Presenting as a Midline Mass on a Chin

Abstract: A 17-month-old boy was evaluated for a midline mass on his chin. The mass was anchored to the mentalis muscle with a stalk-like structure. The pathological diagnosis of the mass was rhabdomyomatous mesenchymal hamartoma. This is the first report of rhabdomyomatous mesenchymal hamartoma presenting as a midline chin mass in Korean pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Most of the STHs present as a single lesion as seen in our cohort, and only two cases to our knowledge have been reported presenting as multiple lesions one of which was in a 2‐day‐old patient with two striated muscle hamartomas, one on the lower back and the other in the right buttock, 39 and in a 15‐year‐old boy with seven nodules on his left cheek 47 . The mean size of our STHs was 5.7 mm (±3.6), which is in keeping with most of the reported cases which are ≤1 cm, 14,36,37,40,49,52,55,57,63,64 with only one of our cases being >1 cm. However, multiple cases have been reported measuring >1 cm 38,39,41‐43,45‐47,50,51,53,54,58 with the largest case to our knowledge measuring 4.9 × 3.5 × 3 cm 60 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Most of the STHs present as a single lesion as seen in our cohort, and only two cases to our knowledge have been reported presenting as multiple lesions one of which was in a 2‐day‐old patient with two striated muscle hamartomas, one on the lower back and the other in the right buttock, 39 and in a 15‐year‐old boy with seven nodules on his left cheek 47 . The mean size of our STHs was 5.7 mm (±3.6), which is in keeping with most of the reported cases which are ≤1 cm, 14,36,37,40,49,52,55,57,63,64 with only one of our cases being >1 cm. However, multiple cases have been reported measuring >1 cm 38,39,41‐43,45‐47,50,51,53,54,58 with the largest case to our knowledge measuring 4.9 × 3.5 × 3 cm 60 …”
Section: Discussionsupporting
confidence: 89%
“…STH most commonly presents in the head and neck as in our cases (11 cases, 91.7%) specifically in the midline chin region 14,37,42,46,57,58,62 . Only one of our cases presented outside of the head and neck region, specifically in the perineum as an inflamed skin tag.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…At the caudal end are seromucinous glands in the dermis layer as well as the characteristic upper respiratory type pseudostratified ciliated epithelium at the sinus ending [7]. CMCC is often initially misinterpreted by physicians as a branchial cleft deformity, TGDC, or other congenital malformations [8,9]. Gargan et al [10] reported 12 misdiagnosed midline cervical cleft cases from 612 thyroglossal diseases and branchial cleft sinus diseases in 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…Though originally called striated muscle hamartoma, it was subsequently coined RMH by Mills in 1989, and has since also been referred to as congenital midline hamartoma 2 . Since its original description, 67 cases have been reported in the literature 3 . RMH presents most commonly in midline sites of the head and neck region in newborns or young children, and is histopathologically characterized by a haphazard dermal proliferation of striated muscle admixed with adipose tissue and adnexal structures.…”
Section: Introductionmentioning
confidence: 99%